Incarcerated giant uterine leiomyoma within an incisional hernia: a case report. Issue 11 (26th September 2017) - Exarchos, Georgios; Vlahos, Nikolaos; Dellaportas, Dionysios; Metaxa, Linda; Theodosopoulos, Theodosios
Key Clinical Message: Uterine leiomyomas presenting as incarcerated or strangulated hernias in surgical emergencies are extremely rare and should be considered in the differential diagnosis in patients with known uterine fibroids and an irreducible ventral abdominal wall hernia. Detailed history and multidisciplinary approach optimize the diagnosis and decision making toward surgical treatment. Abstract : Uterine leiomyomas presenting as incarcerated or strangulated hernias in surgical emergencies are extremely rare and should be considered in the differential diagnosis in patients with known uterine fibroids and an irreducible ventral abdominal wall hernia. Detailed history and multidisciplinary approach optimize the diagnosis and decision making toward surgical treatment.